What have you done? - Lapena, Shari, 1960- ([New York] : Pamela Dorman Books/Viking, 2024)
Nothing ever happens in sleepy little Fairhill, Vermont. But this morning that will change. And one innocent question could be deadly. What have you done? The teenagers get their kicks telling ghost stories in the old graveyard. The parents trust their kids will arrive home safe from school. Everyone knows everyone. Curtains rarely twitch. Front doors are left unlocked. But Diana Brewer isn't lying safely in her bed where she belongs. Instead she lies in a hayfield, circled by vultures, discovered by a local farmer. How quickly a girl becomes a ghost. How quickly a town of friendly, familiar faces becomes a town of suspects, a place of fear and paranoia. Someone in Fairhill did this. Everyone wants answers.
"Simultaneously published in hardcover in Great Britain by Transworld, an imprint of Penguin Random House Ltd., London, in 2024"--Title page verso.
Keywords: Family secrets -- Fiction; City and town life -- Fiction; Teenage girls -- Crimes against -- Fiction; Murder -- Fiction; Vermont -- Fiction; Psychological fiction; Suspense fiction; Psychological fiction; Thrillers (Fiction); Novels